Removal of methylene blue from aqueous solution by adsorption on natural adsorbents / Siti Nur Fadhila Mat Razi - Mat Razi, Siti Nur Fadhila (2008)
Adsorption of methylene blue from aqueous solution using natural adsorbent is one of an alternative to remove color from wastewater. Natural adsorbents, prepared from natural wastes; egg shells, crab shells and cockle shells were used as adsorbent for removal of methylene blue from aqueous solution. The adsorption experiments were conducted on the three types of adsorbents and at different dosage of adsorbent for egg shells and cockle shells. The maximum removal of methylene blue 4.0 x 10"3 M occurred at 20g of adsorbent added. Meanwhile, the most effective removal of methylene blue of adsorbents dose was at 20g. The results indicate that crab shells have be higher percentage of adsorption than egg shells and cockle shells , that mean crab shells is more effective compared to egg shells and cockle shells. The results indicate that natural wastes as an alternative to commercial activated carbon for wastewater treatment.